THE INFLUENCE OF THE PROBLEM BASED LEARNING MODEL ON STUDENTS' LEARNING OUTCOMES - Anita Rahayu; Bambang Hermansyah; Marleni (Esteem Journal of English Education Study Programme, 2024)
The aim of this research is to find out whether there is an influence of the Problem Based Learning (PBL) model on the learning outcomes of science students regarding plant morphology in class IV at Miftahul Jannah Banyuasin. The method used is quasi experimental design, a form of design that uses non-equivalent control group design. The population of this study was all fourth grade students. Meanwhile, the samples in this research were students in classes IV.A and IV.B with a total of 60 students. The data collection technique is carried out using tests. The data analysis technique used is the t test (independent t test). The results of the research show that the results of the hypothesis using the t-test on both groups with the results obtained, the tcount = 3.60 while the ttable value = 2045, thus tcount > ttable (3.60 > 2045) which means the working hypothesis (Ha) in This research was accepted, namely the results of science learning material on plant morphology for class IV students. This proves that there is an influence of the problem based learning model on the science learning outcomes of plant morphology material for class IV MI (Miftahul Jannah) Banyuasin students.